(untitled) (Shaheed Smriti Journal, 2024)
Urbanization results in habitat modification causing alteration in the assemblage of biological diversity. Bird diversity serves as a good ecological indicator; hence, this study examined the effects of urbanization on bird species counting and diversity in East-west highway from Lothar Khola to Tikauli Bufferzone Forest, Chitwan. Bird surveys were conducted during the spring season and pre-monsoon seasons of 2022 along fifteen transects each of 2 km length by positioning the point count stations at every 2 km interval on vehicle survey. A total of 3,147 birds of 63 species were observed from 28 families. Among the 63 species, 58 were residents and 5 were migratory. The associations of bird richness and abundance were found higher in forest area that covers almost 20% of the total surveyed transects. Number of nest were also recorded throughout the entire survey and majority of nest were of Baya weaber. Conversely, road under construction showed negative effects. In an urban setting, 100 nesting sites were recorded on electric pole, tree species and some on the residential houses. Thus, cities should focus on developing green city concept simultaneously with other developmental projects.